2014
DOI: 10.3390/agronomy4010090
|View full text |Cite
|
Sign up to set email alerts
|

Yield Response of Native Warm-Season Forage Grasses to Harvest Intervals and Durations in Mixed Stands

Abstract: Tolerance to frequent defoliations is critical for native warm-season grasses managed for forage and wildlife habitat. Yield response of big bluestem (Andropogon gerardii), indiangrass (Sorghastrum nutans), and little bluestem (Schizachyrium scoparium) to treatments (30-, 40-, 60-, 90-or 120-d harvest intervals) and durations were assessed on early-succession mixed stands. Over three years, phased harvestings were initiated in May, on sets of randomized plots, in five replications to produce one-, two-, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Because harvesting reduced litter buildup uniformly across treatments, lack of differences in percentage bare ground was consistent with similarity in grass cover values implying that harvest intervals had no effect on post-season stand recovery. This was actually consistent with the observed lack of effect of previous-year harvest intervals on the first mid-May forage yield [27].…”
Section: Bare-ground Spacesupporting
confidence: 89%
“…Because harvesting reduced litter buildup uniformly across treatments, lack of differences in percentage bare ground was consistent with similarity in grass cover values implying that harvest intervals had no effect on post-season stand recovery. This was actually consistent with the observed lack of effect of previous-year harvest intervals on the first mid-May forage yield [27].…”
Section: Bare-ground Spacesupporting
confidence: 89%
“…They are also able to sustain high photosynthetic activity during hot and dry summer months due to their C 4 photosynthetic pathway. This ability to sustain growth under harsh growing conditions may explain the observed high annual yields of 2637 kg ha -1 for unfertilized BB, IG, and SG (Mulkey et al, 2008), and 8472 kg ha −1 from mixed stands of BB, IG, and LB (Temu et al, 2014a). In another study, SG yield of 8000 kg ha -1 is reported with 55% of it being obtained in July and August (Jung et al, 1985).…”
Section: Summer Forage Shortagesmentioning
confidence: 79%
“…So, incorporating NWSGs into the pasture systems will most likely improve summer forage production and availability in the region. For over a decade now, the mid-south and southeastern regions of the US have seen a growing interest in NWSGs mainly due to their superior summer forage potential (Angima et al, 2009;Temu et al, 2014a), wildlife habitat quality features (Temu et al, 2014b), and low-input demand. Of the NWSGs, big bluestem (BB, Andropogon gerardii Vitman), eastern gamagrass (GG, Tripsacum dactyloides L.), indiangrass [IG, Sorghastrum nutans (L.).…”
Section: Summer Forage Shortagesmentioning
confidence: 99%
“…Because responses to defoliation often differ among plant species [29], the compositions of mixed stands are usually influenced by their most frequent species. Monitoring how key species respond to harvest regimes is, therefore, helpful to managers interested in improved and/or sustained diversity of desirable species [37]. Except for BB, the occurrence of perennials showed significant year differences (Table 2).…”
Section: Proportions Of Perennial Grass Speciesmentioning
confidence: 99%